2022
DOI: 10.3390/microorganisms10030646
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Diamondback Moth—Increased Efficacy with Mixtures of Beauveria Fungi

Abstract: Diamondback moth (DBM) is an important horticultural pest worldwide as the larvae of these moths feed on the leaves of cruciferous vegetables. As DBM has developed resistance to more than 100 classes of synthetic insecticides, new biological control options are urgently required. Beauveria species are entomopathogenic fungi recognized as the most important fungal genus for controlling a wide range of agricultural, forestry, and veterinary arthropod pests. Previous research, aimed at developing new Beauveria-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Two New Zealand-derived fungal isolates, B. pseudobassiana I12 Damo and B. bassiana CTL20, previously identified with high virulence towards DBM larvae ( Soth et al, 2022 ), were selected for this study. The isolates were sourced from the culture collection held at the Bio-Protection Research Centre (BPRC), Lincoln University, New Zealand.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two New Zealand-derived fungal isolates, B. pseudobassiana I12 Damo and B. bassiana CTL20, previously identified with high virulence towards DBM larvae ( Soth et al, 2022 ), were selected for this study. The isolates were sourced from the culture collection held at the Bio-Protection Research Centre (BPRC), Lincoln University, New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…The isolates were maintained as axenic cultures on PDA (Thermo Fisher Scientific, Waltham, MA, USA; Oxoid Ltd., Basingstoke, UK) at 22 °C until required. The harvest and preparation methods for Beauveria conidia were previously described in Soth et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported synergistic or antagonistic effects on target pests after combining microbial biopesticides (Garbutt et al 2011 ; Hodgson et al 2004 ; Li et al 2021 ; Raymond et al 2008 ). Soth et al ( 2022 ) suggested that combining several genetically distinct isolates might lead to synergistic interactions or overcome environmental constraints. Studies using combinations of the two most applied entomopathogens, Bacillus thuringiensis and Beauveria bassiana , on target pests showed various interactions with different effects, including synergistic (Wraight and Ramos 2005 ; Kryukov et al 2009 ; Xue et al 2018 ), additive (Mwamburi et al 2009 ), or antagonistic (Ma et al 2008 ) depending on the pest and doses (Gao et al 2012 ; Mantzoukas et al 2013 ; Sayed and Behle 2017 ; Wraight and Ramos 2017 ).…”
Section: Introductionmentioning
confidence: 99%